Experimental and Theoretical Studies of synthesized of lower cost choline chloride based deep eutectic solvent composed of crude glycerol as hydrogen bond donor - Anis Usmani (School of Bioprocess Engineering, University Malaysia Perlis, 2016)
Deep eutectic solvent (DES) has been currently developed to assist industrial applications. Basically, DES can be synthesized by components of hydrogen bond acceptor (HBA) and hydrogen bond donor (HBD). In this study, crude glycerol and choline chloride were utilized as starting material for DES synthesized. Purchased bio-based crude glycerol was initially pretreated, purified and utilized as hydrogen bond donor. Purification of crude glycerol using choline chloride in extraction stage, is an effective components improving purification method together with DES forming at 1:2 mole ratio. Moreover, the effect of temperature and water content on density and viscosity within the range of 30 -- 90 C in every 10 degree intervals was investigated, as a result, at 30 C, DES possess density and viscosity of 1.1780 g/cm3 and 378 cp, the good solvent relies on density and viscosity ambient temperature. The increasing of temperature, and water contents in DES, decreases density and viscosity. After all, DES was evaluated in transesterification of cooking oil. Lastly, the present of DES in the reaction increases the efficiency of separation and biodiesel yield with the maximum reusability giving high potential and efficiency of DES is four regenerations. It is worth that crude glycerol was value-added in simple process which significantly giving diverse applications.